An investigation of chirped fibre Bragg gratings Fabry-Perot interferometer for sensing applications - Cheung, Chi Shing (Cranfield University, 2005)
Fibre interferometer configurations such as the Michelson and Fabry-Perot (FP) have been formed using uniformed and chirped Fibre Bragg Gratings (FBG) acting as partial reflectors. As well as increasing the dynamic range of the interferometer, chirped FBGs are dispersive elements which can allow tuning of the response of the interferometers to measurements such as strain and temperature. In a chirped FBG, the resonance condition of the FBG varies along the FBG’s length. Each wavelength is reflected from different portion of the FBG, which imparts a different group delay to the different components of the incident light. The implication of the wavelength dependence resonance position is that there is a large movement of the resonance position when the incident wavelength is changed. A chirped FBG FP can be configured in which the large movement of the reflection positions in the respective FBGs forming the cavity changes in such a way that the sensitivity of the cavity can be enhanced or reduced. The FP filter response can be tailored through the extent of chirp. In this project a theoretical model of the in fibre interferometers formed using chirped FBGs is presented. The model indicates that it is possible to form FP cavities with varying sensitivity to strain and temperature by appropriate choice of chirp parameters and cavity length. An experimental demonstration of a chirped FBG FP cavity with reduced sensitivity to strain. This scheme offers flexibility in determining the sensitivity of the FP sensor to strain, not only through the gauge length but also via the parameters of the chirped FBG pairs, allowing the use of long or short gauge length sensors. It is possible to configure the system to exhibit enhanced sensitivity to strain or alternatively, to have reduced or even zero strain sensitivity. This ability to tailor the sensitivity of the FP via the FBG parameters will enhance the capabilities of FP sensor system.